2021
DOI: 10.1093/jac/dkab335
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of doxycycline versus azithromycin for the treatment of rectal chlamydia: a systematic review and meta-analysis

Abstract: Background Chlamydia trachomatis infection is the most common sexually transmitted infectious disease and carries a risk of complications. However, the optimal treatment for rectal chlamydial infection remains unclear. Objectives To compare the efficacy of doxycycline and azithromycin for the treatment of rectal chlamydia by undertaking a systematic review and meta-analysis of published data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In case 2, treatment with azithromycin appeared to be clinically successful however, azithromycin was given in combination with tetracycline eye ointment after the patient had been treated with chloramphenicol eye drops for two weeks. Treatment failure up to 17 % with this antibiotic regimen has been reported for several infections caused by C. trachomatis , especially in rectal infections [ [19] , [20] , [21] , [22] , [23] ] and the treatment of trachoma in young children. Azithromycin is no longer the first-choice antibiotic for these infections, instead 100 mg doxycycline orally twice a day for between 7 and 21 days is recommended and has been shown to be more effective [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In case 2, treatment with azithromycin appeared to be clinically successful however, azithromycin was given in combination with tetracycline eye ointment after the patient had been treated with chloramphenicol eye drops for two weeks. Treatment failure up to 17 % with this antibiotic regimen has been reported for several infections caused by C. trachomatis , especially in rectal infections [ [19] , [20] , [21] , [22] , [23] ] and the treatment of trachoma in young children. Azithromycin is no longer the first-choice antibiotic for these infections, instead 100 mg doxycycline orally twice a day for between 7 and 21 days is recommended and has been shown to be more effective [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical setting, > 5% chlamydia failures to the treatment with azithromycin have been reported, with resistances up to 23% in men with non-gonococcal urethritis (NGU) treated with 1 g single-dose azithromycin, although reinfection could not be excluded from the study 28,29 . Macrolide resistance suspicion and doxycycline efficacy in treating chlamydia, particularly in extra urogenital sites, have favored current treatment guidelines into using doxycycline as a first-line approach [29][30][31] .…”
Section: Chlamydiamentioning
confidence: 99%
“…Two recent systematic reviews and metaanalyses using Cochrane methodology examined the most effective treatment for urogenital and rectal C. trachomatis infections. 8,9 Páez-Canro et al 8 included 14 studies with a total of 2,147 participants, of which 568 were females aged between 17-60 years. Five studies were included in the meta-analysis that investigated microbiological failure in non-pregnant females; the authors reported that overall, there was insufficient evidence to determine whether doxycycline or azithromycin was the more effective treatment for urogenital C. trachomatis infections (RR 1.71, 95% CI, 0.48 to 6.16).…”
Section: Azithromycin Versus Doxycycline: Management Of Female Urogen...mentioning
confidence: 99%
“…Reported adverse effects were gastrointestinal in nature (nausea, vomiting, abdominal pain). Chen et al 9 reported a 27% increase in risk of microbial failure with azithromycin in rectal C. trachomatis infections (RR 1.27, 95% CI, 1.20, 1.35). Subgroup analyses reported doxycycline consistently provided greater chance of microbial cure irrespective of gender, study design or country where the study was conducted.…”
Section: Azithromycin Versus Doxycycline: Management Of Female Urogen...mentioning
confidence: 99%